Producción de Biochar a partir de materia orgánica de heces de vacunos y porcinos para la recuperación de aguas contaminadas con metales pesados a nivel de laboratorio. - Hualca Barahona, Nathkary Saharai (2023)
Currently, one of the major environmental problems we have is the contamination of water resources by heavy metals generated by different industrial activities. An alternative solution to these problems is the use of biochar, since it is a form of charcoal created by heating biomass, in a low oxygen content environment through a process called pyrolysis. Pyrolysis occurs at high temperatures, generally between 350 and 700 degrees Celsius, which removes volatile compounds and leaves a stable carbon-rich product, i.e. biochar. This is a technological option that has been applied experimentally in water sources, since it improves the physical-chemical characteristics of the water, as well as helps the adsorption of heavy metals present in the form of ions in the water, in other words. , favors the decontamination of water. This research aimed to produce biochar and evaluate the effect of biochar in water specifically contaminated with heavy metals, therefore, biochar was established as an experimental model in the laboratory. The results were obtained through different processes starting with the appropriate selection for the sample.